A modern guide to the multiple streams framework - Zahariadis, Nikolaos; Herweg, Nicole; Zohlnhöfer, Reimut; Petridou, Evangelia (Edward Elgar Publishing, 2023)
"Applying the Multiple Streams Framework (MSF) to a global range of case studies, this pioneering Modern Guide addresses how policymakers decide what issues to attend to and which choices to make or implement. In doing so it outlines that, far from being the exception, ambiguity and timing are integral parts of every comparative explanation of the policy process. Considering the MSF at the theoretical level, contributors assess the assumptions, structure and logic of the framework before examining the scope of reforms, multilevel influence and interaction, coupling as a process, and the motives of policy entrepreneurs. Using a diverse array of cases from around the world at sub-national, national, and international levels of governance, chapters apply the framework to such diverse topics as climate policy in Europe, soil pollution laws in China, pandemic management in Turkey and Bolsonaro's gun liberalization agenda in Brazil. Ultimately, the Modern Guide demonstrates that public policy is a process replete with bias, language and symbols among interacting policy actors who generate conflicting messages in staged settings of political power. Situating the framework within broader debates of the policy process, this innovative Modern Guide will be vital to students and scholars of political science, public policy, and public administration and management. With empirical practical applications which advance the MSF, it will also be of use to policymakers globally"--
Keywords: Einführung; Politische Entscheidung; Agenda setting; Politik